Improved hepatic arterial fraction estimation using cardiac output correction of arterial input functions for liver DCE MRI. (25th January 2017) - Chouhan, Manil D; Bainbridge, Alan; Atkinson, David; Punwani, Shonit; Mookerjee, Rajeshwar P; Lythgoe, Mark F; Taylor, Stuart A
Abstract: Liver dynamic contrast enhanced (DCE) MRI pharmacokinetic modelling could be useful in the assessment of diffuse liver disease and focal liver lesions, but is compromised by errors in arterial input function (AIF) sampling. In this study, we apply cardiac output correction to arterial input functions (AIFs) for liver DCE MRI and investigate the effect on dual-input single compartment hepatic perfusion parameter estimation and reproducibility. Thirteen healthy volunteers (28.7 ± 1.94 years, seven males) underwent liver DCE MRI and cardiac output measurement using aortic root phase contrast MRI (PCMRI), with reproducibility ( n = 9) measured at 7 d. Cardiac output AIF correction was undertaken by constraining the first pass AIF enhancement curve using the indicator-dilution principle. Hepatic perfusion parameters with and without cardiac output AIF correction were compared and 7 d reproducibility assessed. Differences between cardiac output corrected and uncorrected liver DCE MRI portal venous (PV) perfusion ( p = 0.066), total liver blood flow (TLBF) ( p = 0.101), hepatic arterial (HA) fraction ( p = 0.895), mean transit time (MTT) ( p = 0.646), distribution volume (DV) ( p = 0.890) were not significantly different. Seven day corrected HA fraction reproducibility was improved (mean difference 0.3%, Bland–Altman 95% limits-of-agreement (BA95%LoA) ±27.9%, coefficient of variation (CoV) 61.4% versus 9.3%, ±35.5%, 81.7% respectively without correction). Seven day uncorrected PV perfusion was also improved (mean difference 9.3 ml min −1 /100 g, BA95%LoA ±506.1 ml min −1 /100 g, CoV 64.1% versus 0.9 ml min −1 /100 g, ±562.8 ml min −1 /100 g, 65.1% respectively with correction) as was uncorrected TLBF (mean difference 43.8 ml min −1 /100 g, BA95%LoA ±586.7 ml min −1 / 100 g, CoV 58.3% versus 13.3 ml min −1 /100 g, ±661.5 ml min −1 /100 g, 60.9% respectively with correction). Reproducibility of uncorrected MTT was similar (uncorrected mean difference 2.4 s, BA95%LoA ±26.7 s, CoV 60.8% uncorrected versus 3.7 s, ±27.8 s, 62.0% respectively with correction), as was and DV (uncorrected mean difference 14.1%, BA95%LoA ±48.2%, CoV 24.7% versus 10.3%, ±46.0%, 23.9% respectively with correction). Cardiac output AIF correction does not significantly affect the estimation of hepatic perfusion parameters but demonstrates improvements in normal volunteer 7 d HA fraction reproducibility, but deterioration in PV perfusion and TLBF reproducibility. Improved HA fraction reproducibility maybe important as arterialisation of liver perfusion is increased in chronic liver disease and within malignant liver lesions.